Seasonal distribution of Dall's porpoise in Prince William Sound, Alaska. (January 2018) - Moran, John R.; O'Dell, Matthew B.; Arimitsu, Mayumi L.; Straley, Janice M.; Dickson, Danielle M.S.
Abstract: Dall's porpoise, Phocoenoides dalli, are a conspicuous predator in the Prince William Sound ecosystem, yet there has been little effort directed towards monitoring this species since the 1980s, prior to the Exxon Valdez oil spill. We used vessel-based surveys to examine the seasonal distribution of Dall's porpoise in the waters of Prince William Sound during eight years from 2007 to 2015. Over the course of 168 days and 15, 653 km of survey effort, 921 Dall's porpoise were encountered in 210 groups. We estimate an encounter rate of 0.061 porpoise/km traveled or 1 porpoise encountered for every 16.5 km traveled. Dall's porpoise were found throughout the year in Prince William Sound, and used a wide range of habitats, including those not considered typical of the species, such as bays, shallow water, and nearshore waters. Dall's porpoise seasonally shifted their center of distribution from the western passages in fall to the bays of the eastern Sound in winter and spring. Dall's porpoises were widely dispersed throughout the Sound in summer. We identified potential Dall's porpoise habitat (depth, slope, and distance from shore) within Prince William Sound using generalized additive models (GAM). Dall's porpoise were found in deeper water during summer and in shallowest water during spring. We propose that their use of novel habitats is a function of reduced predation risk associated with the decline of their main predator, killer whales ( Orcinus orca ), following the Exxon Valdez oil spill, and the presence of overwintering and spawning Pacific herring ( Clupea pallasii ). While the size of the Dall's porpoise population within Prince William Sound remains unknown, our encounter rates were lower than those reported in the 1970s. Their high metabolic rate and ubiquitous presence makes them one of the more important, yet understudied, forage fish predators in the region.